Identifying an optimal antiemetic regimen for patients receiving anthracycline and cyclophosphamide-based chemotherapy for breast cancer – An inspection of the evidence base informing clinical decision-making. Issue 10 (December 2015) - Hutton, Brian; Clemons, Mark; Mazzarello, Sasha; Kuchuk, Iryna; Skidmore, Becky; Ng, Terry
Highlights: Evidence-base of antiemetic regimens for breast cancer presents challenges. Range of treatments selected based on local practice rather than clinical equipoise. Outcome reporting in randomized trials of antiemetic regimens is highly variable. Future trials should include an assessment of the most comprehensive outcomes. Abstract: Background: Despite consensus recommendations for antiemetics in breast cancer patients receiving anthracycline and cyclophosphamide-based chemotherapy, control of chemotherapy-induced nausea and vomiting (CINV) remains sub-optimal. Objective: To inspect available evidence from randomized controlled trials (RCT) in this population to establish treatment comparisons that have been studied, outcomes that have been reported, and the extent of study heterogeneity. Review of this data helps identify challenges for a systematic review comparing antiemetic regimens, and to identify potential future trials. Methods: A search of Ovid MEDLINE®, Embase and Cochrane CENTRAL was performed. We sought RCTs comparing antiemetic regimens in breast cancer patients receiving anthracycline and cyclophosphamide-based chemotherapy. We extracted information related to study design, patient characteristics and interventions compared. Patterns of outcome reporting were studied. While performing network meta-analysis was also of interest, studies were judged highly heterogeneous and it was felt findings from such work would be of uncertain validity. Results: From 1062 citations, a total of 30 full texts were retained. Overall, 47 antiemetic regimens were evaluated using 15 different CINV endpoints. Treatment comparisons were diverse and many were informed by single small trials. Reporting of key endpoints was varied and all endpoints were not consistently available. Heterogeneity in patients, chemotherapies administered, and intervention doses were noted. Conclusions: Despite the availability of consensus recommendations for antiemetic use, we identified challenges in synthesizing the evidence base including high diversity in treatment comparisons, varied outcome reporting, and study heterogeneity. These represent challenges to identifying an optimal antiemetic regimen. Future antiemetic trials should incorporate more informed comparator selection, report patient-oriented outcomes in a standard fashion, and provide accessible data for these measures.